0356 Associations Between Ethnicity, Socioeconomic Deprivation and Preschoolers' Sleep Health in Aotearoa/New Zealand. (27th May 2020) - Muller, D; Paine, S; Wu, L J; Signal, T L
Abstract: Introduction: In Aotearoa/New Zealand (NZ) ethnic and socioeconomic inequities exist in adult sleep health but less is known about relationships between ethnicity, socioeconomic position and sleep in early childhood. Methods: Maternally-completed questionnaire data from a pregnancy-birth cohort were analysed cross-sectionally. Log-binomial regression models investigated independent associations between ethnicity, socioeconomic position and sleep of 340 Māori (Indigenous) and 570 non-Māori 3-4 year olds. Independent variables included child ethnicity, gender, area-level deprivation (NZDep quintiles; 5=most deprived) and individual-level deprivation (NZiDep scores 1-5; 5=most deprived). Dependent variables included typical weekday and weekend sleep duration (<10hrs/10-13hrs), difference in week/weekend sleep duration (>1hr/≤1hr) and midsleep time (≥1hr/<1hr), problems falling asleep and problematic sleep patterns (no vs. moderate/large problem). Results: Māori preschoolers were more likely to have short sleep (weekdays: PR=2.23, 95% CI 1.31-3.82; weekends: PR=2.04, 95% CI 1.24-3.36), week/weekend sleep duration difference >1hr (PR=2.47, 95% CI 1.59-3.84), week/weekend midsleep difference ≥1hr (PR=2.38, 95% CI 1.30-4.36) and a moderate/large problem falling asleep (PR=1.43, 95% CI 1.00-2.06) than non-Māori preschoolers. Preschoolers living in most deprived areas were more likely to have short sleep on weekdays (NZDep quintile 4: PR=3.91, 95% CI 1.43-10.72; NZDep quintile 5: PR=4.14, 95% CI 1.54-11.12) and week/weekend sleep duration difference >1hr (NZDep quintile 4: PR=2.34, 95% CI 1.23-4.43) than preschoolers in least deprived areas. Children with higher individual-level deprivation scores were more likely to have short sleep on weekends (NZiDep 5: PR=2.38, 95% CI 1.21-4.67) and a moderate/large problem falling asleep (NZiDep 3: PR=1.72, 95% CI 1.10-2.67) compared to children with lowest scores. Conclusion: Ethnic and socioeconomic sleep health inequities exist as early as 3 years of age in NZ. Socio-political drivers of social and economic disadvantage experienced by Māori children and children from families who hold low socioeconomic position must be addressed to achieve equitable sleep health early in the lifecourse. Support: Funding support was provided by Massey University New Zealand (Massey University Strategic Innovation Fund; Massey University Research Fund; and Massey University Doctoral Scholarship) and the Health Research Council of New Zealand (HRC 09/233, 08/547).